Analisis kebangkrutan dengan metode altman z-score, springate, zmijewski dan grover PT. Matahari department store tbk tahun 2016-2021 - Oktaviani, Reza Yetri; Yanti, Mahardini Syahputri (ARKA INSTITUTE, 2022)
This study aims to determine the potential for bankruptcy at PT. Matahari Department Store Tbk., which is measured using the methods, namely the Altman Z-score method, the Springate method, Zmijewski, and Grover. The results of this study are all financial reports of PT Matahari Department Store Tbk., The samples used were taken from the balance sheet and income statement in 2016-2021. The analysis techniques used are the Alman Z-score, Springate, Zmijewski, Grover discriminants. The results obtained during the 6-year period studied at PT Matahari Department Store Tbk showed that in 2020 it had the potential to go bankrupt, but it can be concluded that in general in the 2016-2021 period it was in a healthy condition.